ANALISIS KONTEKS ASAL BUDAYA PAPUA DALAM PENDIDIKAN MATEMATIKA REALISTIK - Mumu, Jeinne; Aninam, Paim (Journal of Honai Math, 2018)
This research is an appreciation of local wisdom of Papuan culture. Various Papuan cultures that have been very united with the Papuan community, such as: Batik Papua, Rumah Kaki Seribu (Traditional House tribe Arfak Mountains), and the habits of eating areca in para-para pinang, are some Papuan cultural products that serve as subjects in this study. The three products of the Papuan culture was analyzed in relation to the mathematical concept so that it becomes a realistic context in this research. The results showed that the three elements of culture can be used as a context in realistic mathematics education in the land of Papua. DOI: https://doi.org/10.30862/jhm.v1i1.768